Retinoblastoma in Jordan, 2003–2013: Ocular Survival and Associated Factors. (December 2014) - Al-Nawaiseh, Ibrahim; Jammal, Hisham M.; Khader, Yousef S.; Jaradat, Imad; Barham, Rasha
Abstract Purpose: To determine ocular survival and factors affecting globe survival in patients diagnosed with retinoblastoma at King Hussein Cancer Center (KHCC). Methods: A retrospective review of medical records of 71 Jordanian patients (45 males and 26 females) diagnosed with retinoblastoma (114 eyes) between June 2003 and May 2013 was conducted. Patient sociodemographic and relevant characteristics were collected from records. Patients with bilateral retinoblastoma were treated with chemoreduction and focal consolidation. Lens-sparing radiation therapy and enucleation were reserved for eyes that failed chemoreduction combined with focal therapy. In cases of unilateral retinoblastoma, primary enucleation was recommended for eyes with advanced unilateral disease (Reese-Ellsworth classification groups IV and V). Kaplan-Meier survival and Cox regression multilevel analysis were used to analyze the data. Results: Median age at diagnosis was 12 months. The follow-up period ranged from 0.25–160 months (mean 26.9 months). The Kaplan–Meier estimate of globe survival of the 114 eyes was 68.0% at 1 year, 63.3% at 2 years, and 62.1% at 5 years. The mean survival time was 101.6 months (95% confidence interval, CI, 87.6–115.6 months). In multivariable-adjusted analysis, advanced stage of the disease (hazard ratio, HR, 5.1, 95% CI 2.3–11.6), unilateral disease (HR 3.3, 95% CI 1.4–8.1), and delay in diagnosis (HR 2.4, 95% CI 1.1–5.5) were significantly associated with increased hazard of enucleation. Conclusion: The overall ocular survival rate for eyes with retinoblastoma was close to regional and international figures. Disease stage, laterality, and delay in diagnosis were significant predictors of enucleation.